Ovarian cancer stem cells and their role in drug resistance - Pieterse, Z.; Amaya-Padilla, M.; Singomat, T.; Binju, M.; Madjid, B.; Yu, Y.; Kaur, Pritinder (Pergamon, 2019)
Ovarian cancer is typically diagnosed at advanced stages (III or IV), with metastasis ensuing at stage III. Complete remission is infrequent and is not achieved in almost half of the women diagnosed with ovarian cancer. Consequently, management and treatment of this disease is challenging as many patients are faced with tumour recurrence disseminating to surrounding organs further complicated with acquired chemo-resistance. The cancer stem cell theory proposes the idea that a drug resistant subset of tumour cells drive tumour progression, metastasis and ultimately, recurrent disease. In the ovarian cancer field, cancer stem cells remain elusive with significant gaps in our knowledge. The characteristics and specific role of ovarian cancer stem cells in recurrence still requires further research since different studies often arrive at contradictory conclusions. Here we present a review and critical analysis of current research conducted in the field of ovarian cancer stem cells and their potential role in drug resistance including several signalling pathways within these cells that affect the viability of targeted therapies.